Some hematological values and alpha-naphthyl acetate esterase (ANAE)-positive lymphocyte ratios in Jaydara sheep - Dönmez, Nurcan; Dönmez, Hasan Hüseyin; Kisadere, Ihsan; Kadiralieva, Nariste (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The objective of the study was to evaluate the some hematological values and ANAE-positive lymphocyte ratio of Jaydara sheep in Kyrgyzstan. The availability of information on hematological and biochemical parameters is essential to research conducted with an aim to increase yields in animal production. Materials and methods: The investigation was carried out on 60 healthy sheep aged between 2-3 years old. Leucocyte and erythrocyte counts, hemoglobin levels, hematocrit, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), differential leucocyte ratios and ANAE-positive lymphocyte ratios were investigated in blood samples using an automated cell counter machine. Results: The leucocyte count in Jaydara sheep was found to 4.92±0.59 x 103/mm3. Similarly, erythrocyte count was 11.73±0.65 x 103/mm3. On the other hand, hemoglobin content in blood was 11.70±0.51 gm/dL. The hematocrit, MCV, MCH, and MCHC values were 30.02±1.70 %, 25.64±1.28 µ3, 10.68±0.59 pg and 41.76±2.31% respectively. The differential leucocyte counts in Jaydara sheep were 42.53±1.13 (Neutrophil), 52.61±1.08 (Lymphocyte), 2.75±0.55 (Monocyte), 1.58±0.17 (Eosinophil), and 0.52±0.52 (Basophil). The ANAE-positive lymphocyte ratios in Jaydara sheep was found to be 65.00±2.55. Conclusion: The hematological parameters in healthy Jaydara sheep can be used as reference values for this particular sheep breed in future. http://dx.doi.org/10.5455/javar.2016.c124